Representacao grafica de dados multidimensionais com o auxilio de microcomputador - Cozin, L. F.; Landim, P. M B (My University, 1990)
Software in BASIC (GWBASIC, version 2.0) and TURBO PASCAL (version 3.0) is presented for PC type microcomputers with the purpose of calculating the graphical method for multivariate data according to Andrews. Applying both softwares to data from the Irati Formation mesossaurides skull measures, in velocity and graphical quality, the TURBO PASCAL language performed better. -after English summary
The graphical representation of multivariate data using a microcomputer
Keywords: BASIC; computer program; graphical display; multivariate statistics; TURBO PASCAL